Anatomical Mapping: Mapping the Multi‐Directional Mechanical Properties of Bone in the Proximal Tibia (Adv. Funct. Mater. 46/2020). (12th November 2020) - Munford, Maxwell J.; Ng, K. C. Geoffrey; Jeffers, Jonathan R. T.
Abstract : Bone is a remarkable material with remodeling capabilities stimulated by its loading environment. Refined knowledge of the mechanical environment of bone would allow for the design of regenerative orthopedic implants that control the strain response of surrounding bone. In article number 2004323, Maxwell J. Munford, K. C. Geoffrey Ng, and Jonathan R. T. Jeffers quantify the distribution and behavior of cancellous bone mechanical properties in the proximal tibia.